2020
DOI: 10.1080/03610926.2019.1709646
|View full text |Cite
|
Sign up to set email alerts
|

Detecting long-range dependence with truncated ratios of periodogram ordinates

Abstract: We propose new tests for testing hypotheses about the memory parameter that are based on ratios of periodogram ordinates. They are highly robust against conditional heteroskedasticity and outliers and are therefore of great value for the detection of long-range dependence in financial data. The robustness is obtained by truncation of a distribution with nonexistent moments. Tables of critical values are provided. The performance of the new tests is assessed by extensive simulations. Applying the tests to daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Finally, note that the results from Table 5 are in line with the ones from Mangat and Reschenhofer (2020). The authors use some of the semiparametric estimators considered in this study along with the small-sample estimator developed by Reschenhofer and Mangat (2020). Using the same sampling frequency and bandwidth, the authors found that global and regional temperature series fall into the nonstationary range.…”
Section: Robustness Exercisessupporting
confidence: 69%
“…Finally, note that the results from Table 5 are in line with the ones from Mangat and Reschenhofer (2020). The authors use some of the semiparametric estimators considered in this study along with the small-sample estimator developed by Reschenhofer and Mangat (2020). Using the same sampling frequency and bandwidth, the authors found that global and regional temperature series fall into the nonstationary range.…”
Section: Robustness Exercisessupporting
confidence: 69%
“…Assuming that fractal dynamics does in fact exist in precious metal returns, they explored possible trading strategies that are based on local estimates of H. In contrast, Reschenhofer et al [66] found no evidence of long-range dependence, neither in stock index returns nor in gold returns. Mangat and Reschenhofer [40] and Reschenhofer and Mangat [41] prices, but also at the log absolute returns. Using log absolute returns instead of absolute returns or squared absolute returns for the investigation of volatility has the advantage that we do not have to work with extremely skewed distributions.…”
Section: Resultsmentioning
confidence: 99%